Thiobacillus Ferrooxidans Adaptation substrates formed with pyritic mineral species - Arias A., Vladimir (2013)
In the processes of dissolution and adsorption of metals, the contribution of bacterial species previously adapted to specific environments, in order to achieve good results are required. In adapting Thiobacillus strains exist various mechanisms and reagents, as is the use of substances containing ideal nutrient media according to the effectiveness to achieve. For this reason we have modified the Middle 9k, with the aim of finding an appropriate means thereby increasing bacterial population isolated from strain Thiobacillus ferrooxidans Mining Salvage Unit, modifying the content of iron sulphate in the substrate and the strict control of pH . These values being 22.4 g / Lt iron sulfate and a pH of 1.8 A working conditions in the first 48 hours consumption of hydrogen protons is generated, which reduces acidity 2.3 - 2.4, with much less effect at low substrate concentrations. The production of sulfuric acid by the indirect mechanism of bacterial oxidation is appreciable 3rd day on stabilizing the pH between 1.9 to 2.0 being the most acidic those higher content of substrate (44.4 g /l). Furthermore, the precipitation of iron occurs depends hydrosulfides positively pH and iron sulphate production means will always precipitates, depending on the amount of added substrate, which is reduced by controlling the acidity of the medium and avoid inhibition of the bacteria during the biooxidation process minerals.